The effects of ketamine on prefrontal glutamate neurotransmission in healthy and depressed subjects - Abdallah, Chadi G. (Neuropsychopharmacology, 2018)
The ability of ketamine administration to activate prefrontal glutamate neurotransmission is thought to be a key mechanism contributing to its transient psychotomimetic effects and its delayed and sustained antidepressant effects. Rodent studies employing carbon-13 magnetic resonance spectroscopy ((13)C MRS) methods have shown ketamine and other N-methyl-D-aspartate (NMDA) receptor antagonists to transiently increase measures reflecting glutamate–glutamine cycling and glutamate neurotransmission in the frontal cortex. However, there are not yet direct measures of glutamate neurotransmission in vivo in humans to support these hypotheses. The current first-level pilot study employed a novel prefrontal (13)C MRS approach similar to that used in the rodent studies for direct measurement of ketamine effects on glutamate–glutamine cycling. Twenty-one participants (14 healthy and 7 depressed) completed two (13)C MRS scans during infusion of normal saline or subanesthetic doses of ketamine. Compared to placebo, ketamine increased prefrontal glutamate–glutamine cycling, as indicated by a 13% increase in (13)C glutamine enrichment (t = 2.4, p = 0.02). We found no evidence of ketamine effects on oxidative energy production, as reflected by (13)C glutamate enrichment. During ketamine infusion, the ratio of (13)C glutamate/glutamine enrichments, a putative measure of neurotransmission strength, was correlated with the Clinician-Administered Dissociative States Scale (r = −0.54, p = 0.048). These findings provide the most direct evidence in humans to date that ketamine increases glutamate release in the prefrontal cortex, a mechanism previously linked to schizophrenia pathophysiology and implicated in the induction of rapid antidepressant effects.